2008
DOI: 10.1152/ajpcell.00227.2008
|View full text |Cite
|
Sign up to set email alerts
|

Probenecid, a gout remedy, inhibits pannexin 1 channels

Abstract: Probenecid is a well-established drug for the treatment of gout and is thought to act on an organic anion transporter, thereby affecting uric acid excretion in the kidney by blocking urate reuptake. Probenecid also has been shown to affect ATP release, leading to the suggestion that ATP release involves an organic anion transporter. Other pharmacological evidence and the observation of dye uptake, however, suggest that the nonvesicular release of ATP is mediated by large membrane channels, with pannexin 1 bein… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
384
1
5

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 379 publications
(402 citation statements)
references
References 56 publications
12
384
1
5
Order By: Relevance
“…Pannexin1 is expressed in human RBCs and has recently been suggested to operate as the ATP release channel in erythrocytes [12,28,29]. To assess the effect of pannexin 1 on ATP release, carbenoxolone and mefloquine were used as antagonists for pannexin 1 [30,31]. The results showed that inhibition of pannexin 1 did not decrease the release of ATP (Figure 6(e,f)), indicating that ATP was not released via pannexin1.…”
Section: Resultsmentioning
confidence: 99%
“…Pannexin1 is expressed in human RBCs and has recently been suggested to operate as the ATP release channel in erythrocytes [12,28,29]. To assess the effect of pannexin 1 on ATP release, carbenoxolone and mefloquine were used as antagonists for pannexin 1 [30,31]. The results showed that inhibition of pannexin 1 did not decrease the release of ATP (Figure 6(e,f)), indicating that ATP was not released via pannexin1.…”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, ATP released into narrow extracellular spaces as in the nervous system would be subject to the feedback inhibition. Thus activation of Panx1 channels by ATP through purinergic receptors would not necessarily result in cell death, a phenomenon nevertheless observed upon massive and prolonged stimulation and blockable by the Panx1 channel inhibitor probenecid [10,16].…”
Section: Fig 4 Effect Of Bzatp On Membrane Currents In Oocytes Exprementioning
confidence: 99%
“…Also, the pharmacology of Panx1 channels matches that of ATP release. Almost all compounds that are reported to inhibit non-vesicular ATP release are effective on the Panx1 channel including connexin mimetic peptides and the inhibitor of the organic anion transporter probenecid [15,16]. Finally, the Panx1 channel is controlled by ATP via a negative feedback loop [17].…”
Section: Introductionmentioning
confidence: 99%
“…In a pharmacological test for the involvement of OATs or OATPs in the permeation of phalloidin in the utricle, we used probenecid, which inhibits many OATs and OATPs (Sugiyama et al 2001;Yasui-Furukori et al 2005;Jorgensen et al 2007;Silverman et al 2008). Consistent with a potential involvement for OATPs or OATs in the permeation of phalloidin, probenecid significantly inhibited phalloidin permeation and decreased fluorescence by 33.9 % (Student's t-test, t(16)=3.472, p=0.0003, Fig.…”
Section: Evaluation Of Oatps In the Permeation Of Phalloidin In The Imentioning
confidence: 99%
“…Besides OATs and OATPs, probenecid also inhibits pannexin channels (Silverman et al 2008;Sandilos and Bayliss 2012). Pannexins are transmembrane proteins closely related to the gap-junction forming connexins (Baranova et al 2004).…”
Section: Evaluation Of Oatps In the Permeation Of Phalloidin In The Imentioning
confidence: 99%